Between debt and social inclusion. An analysis of the financialization of argentina´s welfare policy (1983-2019). - Nougues, Tomas (2020)
This article analyzes the transformations of Argentina´s social welfare policies in the last four decades. It focuses in a new type of policy in which the main feature is the employment of credit as a key instrument to meet social needs, which here are called social policies of indebtedness. The consequence of credit adoption is the establishment of a debt relationship between the State —positioned as creditor— and the beneciary —turned into a debtor— that modifes the logics of classical social policy.